Identification of Problem Solving Pattern of Physics Based on Students Personality - Ragil Meita Alfathy; Budi Astuti; Suharto Linuwih (Variabel, 2018)
Studies that reveal the patterns of problem solving have been widely practiced, but there is no studies have revealed a pattern of problem solving based on personality types especially in the field of physics. The aims of this study are to determine the patterns of physics problem solving based on student personality type. The method that used in this research is descriptive qualitative research with Investigation of Lived Experience type. Subjects in this study are 12th-grade science programs students of MAN 1 Banyumas that was determined by a stratified sampling approach. This sampling divides students into homogeneous groups based on Keirsey's four personality types, they are Guardian, Artisan, Rational and Idealist. Each personality type was chosen by nine students as the subject of the study which was determined using a purposive sampling technique. The results showed that the pattern of physics problem solving between Idealist, Artisan, Guardian, and Rational students consecutively are conceptual problem solving, intuitive-analogic problem solving, intuitive problem solving, and analogic problem solving.